2007
DOI: 10.1590/s1519-69842007000500008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of Conopophaga lineata (Conopophagidae) (Wied-Neuwied, 1831) in Atlantic Forest fragments

Abstract: Forest fragmentation affects bird populations in many ways, modifying the composition of communities and favouring open country species. The Atlantic Forest is considered one of the most important biomes in the world, due to its great biodiversity, accelerated rates of deforestation, and high endemism. Despite these characteristics, few studies have evaluated the effects of forest fragmentation in the genetic structure of Atlantic forest bird populations. So, this study aims to verify the effects of forest fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Thus, barriers observed for some endemic taxa from the Atlantic Forest may have acted as selective ecological filters, wherein species with higher tolerance to habitat fragmentation were able to maintain gene flow or disperse across these barriers. Contrary to expected, C. lineata is a species relatively tolerant of habitat fragmentation (Dantas et al 2007) that showed a clear signal of population structure. On the other hand, Cabanne et al (2012) suggested that canopy birds tend to be less genetically differentiated than understory birds, a likely explanation for the genetic structure observed in C. lineata.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Thus, barriers observed for some endemic taxa from the Atlantic Forest may have acted as selective ecological filters, wherein species with higher tolerance to habitat fragmentation were able to maintain gene flow or disperse across these barriers. Contrary to expected, C. lineata is a species relatively tolerant of habitat fragmentation (Dantas et al 2007) that showed a clear signal of population structure. On the other hand, Cabanne et al (2012) suggested that canopy birds tend to be less genetically differentiated than understory birds, a likely explanation for the genetic structure observed in C. lineata.…”
Section: Discussionmentioning
confidence: 77%
“…This species is distributed in tropical and subtropical forests of South America (Sigrislt 2005), from Paraguay and northeast Argentina to northeast Brazil (Sick 1997;Whitney 2003). Despite its large distribution, and remarkable geographical variation in song and plumage (Whitney 2003), few studies have investigated this species (Willis et al 1983;Dantas et al 2007;Dantas et al 2009). Three subspecies are recognized: C. l. cearae is found in northeastern Brazil, from Ceará to Pernambuco; C. l. lineata occurs from Pernambuco to southern Bahia, Central Brazil, in southern Goiás and northern Mato Grosso do Sul; and C. l. vulgaris is found in southeastern Brazil, from southern Espírito Santo to Rio Grande do Sul; eastern Paraguay, Misiones and eastern Uruguay (Whitney 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Bates et al (1999) and Bates (2000) also found substantial levels of genetic differentiation among Amazonian passerine populations in a continuous forest at a local scale (sites 200 km apart), which were explained by the sedentary nature of the studied species. On the other hand, Dantas et al (2007) did not find significant genetic structuring in the congener Conopophaga lineata (Wied, 1831) in semideciduous Atlantic Forest fragments of Minas Gerais State, even when RAPD markers were applied to populations that were more than 600 km apart. Likewise, McDonald (2003) found relatively low levels of genetic differentiation between two populations of Long-tailed Manakin, Chiroxiphia linearis (Bonparte, 1838), in Costa Rica, between a mid-elevation (1,300 m) and a sea-level site separated by 115 km, using microsatellite markers.…”
Section: Statistical Analysesmentioning
confidence: 94%
“…Even though apparently low, this value suggests that, in general, there is a lot of gene flow in the forest fragments studied. Support for this statement comes from genetic analyses indicating that populations of Conopophaga lineata from Atlantic Forest have not been effected by fragmentation (Dantas et al 2007). This result is important if we consider that isolated populations may suffer from inbreeding depression (Ralls et al 1986;Primack 1993).…”
Section: How Much Exchange Of Individuals and Gene Flow Exists Among mentioning
confidence: 99%